PENINGKATAN PEMAHAMAN LATIHAN FISIK BAGI PENYANDANG DISABILITAS FISIK DI BOJONEGORO MELALUI PELATIHAN INCALCY-PHITY - Ashadi, Kunjung; Wiriawan, Oce; Purnomo, Mochammad; Sifaq, Aghus; Ainin, Ima Kurrotun (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The lack of sufficient understanding about physical activity make the lifestyle of people with physical disabilities in Bojonegoro Regency is in a poor quality. This problem is caused by there is nothing of parties who pay attention to the lifestyle of people with disabilities, whether from the government, organizations, society or families. This then has an impact on the quality of life, health, motivation and awareness of the importance of physical activity among people with disabilities. The INCALCY-PHITY training was attended by 20 people with physical disabilities consisting of people with upper and lower body physical disabilities. The method used in this training activity uses an approach in the form of delivering INCALCY-PHITY theory material orally and direct physical activity practice activities. The materials used in this activity are powerpoint material in the theory delivery session and video tutorials for doing sports independently for people with physical disabilities. After participating, all participants stated that they really enjoyed this activity, and that this training could have a positive impact and influence on improving their health and lifestyle in the future